2020
DOI: 10.1371/journal.pone.0237358
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of amide proton transfer-weighted MRI of cerebral infarction with clinico-radiological findings

Abstract: Objective To clarify the relationship between amide proton transfer-weighted (APTW) signal, which reflects intracellular pH, and clinico-radiological findings in patients with hyperacute to subacute cerebral infarction. Materials and methods Twenty-nine patients (median age, 70 years [IQR, 54 to 74]; 15 men) were retrospectively examined. The 10th, 25th, 50th, 75th, and 90th percentiles of APTW signal (APT 10 , APT 25 , APT 50 , APT 75 and APT 90 , respectively) were measured within the infarction region-of-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
(64 reference statements)
2
20
0
Order By: Relevance
“…Figure 3 shows representative APT images of ischemic stroke patients adapted from the included studies (26,29,30,33,40,43). Generally, the clinical studies shared the consensus that APT effect in ischemic tissue (inclusive of the ischemic core, penumbra, and benign oligemia) is smaller compared to normal healthy tissue in early stroke imaging.…”
Section: Apt Effect In Ischemic Lesionsmentioning
confidence: 92%
See 4 more Smart Citations
“…Figure 3 shows representative APT images of ischemic stroke patients adapted from the included studies (26,29,30,33,40,43). Generally, the clinical studies shared the consensus that APT effect in ischemic tissue (inclusive of the ischemic core, penumbra, and benign oligemia) is smaller compared to normal healthy tissue in early stroke imaging.…”
Section: Apt Effect In Ischemic Lesionsmentioning
confidence: 92%
“…The number of published clinical studies showed a gradual increase over the years. In the 14 studies, a total of 282 patients had been scanned with APT imaging after accounting for those judged to be duplicate analyses (using the same patient data but for different purposes); the study by Harston et al (33) and two studies by Msayib et al (34,35) (26,(33)(34)(35)(36)(37), three studies involved only acute stroke patients (29,38,39), one study included both hyperacute and acute patients (40), two studies involved acute and early subacute patients (41,42), while two studies involved patients from the hyperacute to early subacute stages (30,43). Further information on these studies such as the treatment received by patients, scanner field strength, radio frequency (RF) saturation scheme, imaging acquisition parameters, image acquisition time, APT effect quantification method, and other MRI sequences acquired, are presented in https://cdn.amegroups.cn/static/public/qims-20-1339-1.…”
Section: Clinical Studies From 2003-2020mentioning
confidence: 99%
See 3 more Smart Citations